Middle classes, mestizos and migrants: Residential strategies in departmental club’s associates during the 1970-1980 decades in Lima - Gago Hidalgo, Danilo (2024)
This article explores two major issues in Lima: social classes and the middle classes neighborhoods. In a context of urban unpredictability, it addresses the residential strategies carried out by ancashinos, puneños and huancaínos during the 1970 and 1980 decades in Lima. Reviewing the residential criteria, as the material neighborhoods conditions, the urban location and the resident families features, it was identified that social class, ethnic group and social origin were fundamental categories when choosing neighborhoods. The household strategies allow to delve into the homogeneity of the city’s central area, as well as to explore the social differences within the middle classes.